5, 6-Biheterocyclic pentazolate salts as promising energetic materials: a new design strategy. (December 2022) - Wang, Hao-Ran; Zhang, Chong; Sun, Cheng-Guo; Hu, Bing-Cheng; Ju, Xue-Hai
Abstract: Pentazole ( cyclo -N5 − ) energetic salts have always been of high research value in the energetic materials field. However, the low density of the available cyclo -N5 − salt seriously affects its comprehensive performance. Therefore, it is of great significance to effectively design and screen out pentazole salts with excellent properties. In this work, a cation design strategy based on a 5, 6-biheterocycle is proposed. Based on the predicted density, heat of formation and detonation properties, the nitrogen-rich bicyclic heterocycle with -N-O − bond and -NO2 or -NHNO2 substituent as a cation is an effective method to improve the comprehensive properties of cyclo -N5 − salts, and four salts of F2, G2, H2 and H7 with superior comprehensive properties to RDX were selected. Monte Carlo method was used to predict the stable crystal structure of four salts. Atoms in molecules theory (AIM) was used to expound the contribution of hydrogen bond and π-π superposition to the stability of cyclo -N5 − . The cohesive energy density and mechanical properties show that the thermal stability of H2 (with best detonation performance of D : 9.16 km s −1, P : 38.52 GPa) is similar to 3, 6, 7-triamino-7 H -[1, 2, 4]triazolo[4, 3- b ][1, 2, 4]triazol-2-ium pentazolate (decomposition temperature: 394.1 K, impact sensitivity: greater than 40 J). First-principles molecular dynamics simulation for H2 thermal decomposition was performed to explore the underlying mechanism of its excellent detonation performance. This work is expected to provide inspiration for the design and synthesis of cyclo -N5 − salts. Graphical Abstract: ga1